Advocating for Ourselves, Advocating for Our Communities: Canadian Counselling Psychology Into the Next Decade and Beyond: English - Bedi, Robinder P.; Domene, José F.; Kassan, Anusha; Wada, Kaori (Canadian Journal of Counselling and Psychotherapy, 2020)
This special issue of Canadian Journal of Counselling and Psychotherapy is an outgrowth of the landmark 2018 Canadian Counselling Psychology Conference called “Advocating for Ourselves, Advocating for Our Communities: Canadian Counselling Psychology Into the Next Decade and Beyond.” This conference centred on seven working groups: the future of counselling psychology education and training in Canada, foregrounding clinical practice and clinical supervision within the field of Canadian counselling psychology, student advocacy in Canadian counselling psychology, responding to the TRC in Canadian counselling psychology, internationalization of counselling psychology, the role of Canadian counselling psychology in advocating for the needs of members of under-represented groups, and the responsibility of Canadian counselling psychology to reach systems, organizations, and policy-makers. This introduction highlights the seven articles included in this special issue, each of which summarizes the discussion included within one working group and elaborates upon topics that emerged within each working group discussion. We expect that, after reading the articles contained within this special issue, readers will be able to experience some of the intellectual stimulation and inspiration felt by many who attended the working groups in person. We also hope that this collection of articles will inspire those who did not attend the conference to advocate for and to help increase the presence and the influence of Canadian counselling psychology locally, provincially, nationally, and globally as it seeks to promote the best interests of the various communities it serves.